A Survey of Rabbit Handling Methods Within the United Kingdom and the Republic of Ireland. Issue 3 (3rd July 2019) - Oxley, James Andrew; Ellis, Clare Frances; McBride, E. Anne; McCormick, Wanda Denise
ABSTRACT: Rabbits are commonly kept in a variety of settings, including homes, laboratories, and veterinary clinics. Despite the popularity of keeping this prey species, little research has investigated current methods of handling. The aim of this study was to examine the experience of caregivers (owners and keepers) in using five handling methods commonly referred to in books written for companion animal (pet) owners and veterinary and/or laboratory personnel. An online survey was completed by 2644 respondents, representing all three of these groups, and breeders. Data were acquired to determine sources that participants used to gain knowledge of different handling methods, the methods they used and for what purposes they used them, and their perceptions of any associated difficulties or welfare concerns. Results indicated that participants most frequently used the method of supporting a rabbit's body against a person's chest, which was considered the easiest and most welfare-friendly method of the handling methods explored. "Scruffing with rear support" was the least used method and was considered to be distressing and painful for the rabbit. As rabbits are a terrestrial prey species, being picked up is likely an innately stressful experience. Additional research is encouraged to explore the experience of rabbits during handling to identify methods that can be easily used with the fewest welfare compromises.